The Snyder-de Sitter scalar φ⋆4 quantum field theory in D=2 - Franchino-Viñas, Sebastián; Mignemi, Salvatore (Nuclear physics. B, Particle physics, 2022)
We study the two-dimensional version of a quartic self-interacting quantum scalar field on a curved and noncommutative space (Snyder-de Sitter). We show that the model is renormalizable at the one-loop level and compute the beta functions of the related couplings. The renormalization group flow is then studied numerically, arriving at the conclusion that noncommutative-curved deformations can yield both relevant and irrelevant contributions to the one-loop effective action.